Three essays on self-esteem and retirement planning behaviors - Sages, Ronald Alan (Kansas State University, 2012)
This dissertation, consisting of three studies, explores the influence of self-esteem upon retirement planning behaviors. Data for all three essays was obtained from the National Longitudinal Survey of Youth 1979 cohort (NLSY79). A Theory of Self-Esteem (Cast & Burke, 2002) served as a theoretical framework for each study. The first essay examined the association between information search behaviors and retirement planning actions upon two dimensions of self-esteem, consisting of efficacy and worth. Both information search behaviors and retirement planning actions were found to be associated with both dimensions. Attained levels of education and the masculine gender were also found to be significantly associated with each self-esteem dimension. Essay two explored creditworthiness as part of the identity self-verification (Stryker, 1980) and self-esteem buffer mechanism, and its association with pre-retirement planning behaviors. Higher levels of self-esteem, attained level of education, net worth, and net income were all found to be associated with individuals who were likely to engage in one or more preretirement planning behavior. Creditworthy practices, however, were not found to be associated with pre-retirement planning behaviors in this study. Essay three postulated that respondents who possessed a composite psychosocial profile consisting of Rosenberg’s self-esteem scale (Rosenberg, 1965), Pearlin’s mastery scale (Pearlin & Schooler, 1978), and Rotter’s locus of control scale (Rotter, 1966) would be associated with engaging in one or more retirement planning behavior. Results showed that a composite psychosocial profile is associated with individuals likely to engage in one or more retirement planning behaviors. Attained levels of education, net worth, net income, and age were found to be associated with individuals likely to engage in one or more retirement planning behaviors. Results of these three studies demonstrate that an association exists between self-esteem and retirement planning behaviors. This study offers the first exploration of A Theory of Self-Esteem (Cast & Burke, 2002) in a consumer finance context since the theory’s establishment ten years ago. These findings are important to academicians, financial planners, financial counselors, financial therapists, and policymakers in developing future research, strategies for financial success, and in the formulation of public policy to promote personal financial well-being.
Keywords: Self esteem; Retirement planning; Psychosocial profile; Psychology, Behavioral (0384); Social Research (0344)